Adolescent: provider connectedness and STI risk reduction following a brief alcohol intervention: findings from a randomized controlled trial - Dash, Genevieve F.; Bryan, Angela D.; Yang, Manshu; Chung, Tammy; Hudson, Karen A.; Feldstein Ewing, Sarah W. (Frontiers in Psychology, 2023)
Objective. Given the frequent co-occurrence between alcohol use and sexual behavior among adolescents, alcohol interventions may play a role in helping prevent sexually transmitted infections (STIs) in this age group. Psychotherapy “common factors” are one potential active ingredient in intervention efficacy. Thus, the purpose of this study was to evaluate the influence of a critical common factor, adolescent:provider connectedness, on STI risk reduction at 3 months post-intervention. Methods. Community-based youth (N=168) were randomized to two 60-minute individual sessions of either motivational interviewing (MI) or brief adolescent mindfulness (BAM). Logistic regressions predicted post-intervention positive STI from adolescent:provider connectedness, intervention condition, and their interaction. Path analytic models tested post-intervention hazardous drinking as a mediator of the association between adolescent:provider connectedness and reduction in STI risk at 3-month follow-up. Results. Stronger adolescent:provider connectedness reduced risk of STI at 3 months post-intervention, with no differences by treatment condition. A mediational relationship between adolescent:provider connectedness and STI risk via hazardous drinking was not observed. Conclusions. Psychotherapeutic common factors, including adolescent:provider connectedness, may be important in mitigating adolescent health risk in behavioral interventions, above and beyond intervention condition and beyond the target behavior of the intervention.